Chronic Pancreatitis: Pediatric and Adult Cohorts Show Similarities in Disease Progress Despite Different Risk Factors. Issue 4 (April 2019) - Schwarzenberg, Sarah J.; Uc, Aliye; Zimmerman, Bridget; Wilschanski, Michael; Wilcox, C. Mel; Whitcomb, David C.; Werlin, Steven L.; Troendle, David; Tang, Gong; Slivka, Adam; Singh, Vikesh K.; Sherman, Stuart; et al.
ABSTRACT: Objectives: The aim of the present study was to investigate the natural history of chronic pancreatitis (CP); patients in the North American Pancreatitis Study2 (NAPS2, adults) and INternational Study group of Pediatric Pancreatitis: In search for a cuRE (INSPPIRE, pediatric) were compared. Methods: Demographics, risk factors, disease duration, management and outcomes of 224 children and 1063 adults were compared using appropriate statistical tests for categorical and continuous variables. Results: Alcohol was a risk in 53% of adults and 1% of children ( P < 0.0001); tobacco in 50% of adults and 7% of children ( P < 0.0001). Obstructive factors were more common in children (29% vs 19% in adults, P = 0.001). Genetic risk factors were found more often in children. Exocrine pancreatic insufficiency was similar (children 26% vs adult 33%, P = 0.107). Diabetes was more common in adults than children (36% vs 4% respectively, P < 0.0001). Median emergency room visits, hospitalizations, and missed days of work/school were similar across the cohorts. As a secondary analysis, NAPS2 subjects with childhood onset (NAPS2-CO) were compared with INSPPIRE subjects. These 2 cohorts were more similar than the total INSPPIRE and NAPS2 cohorts, including for genetic risk factors. The only risk factor significantly more common in the NAPS2-CO cohort compared with the INSPPIRE cohort was alcohol (9% NAPS2-CO vs 1% INSPPIRE cohorts, P = 0.011). Conclusions: Despite disparity in age of onset, children and adults with CP exhibit similarity in demographics, CP treatment, and pain. Differences between groups in radiographic findings and diabetes prevalence may be related to differences in risk factors associated with disease and length of time of CP. Abstract : Supplemental Digital Content is available in the text